Modifying graphene oxide with short peptide via click chemistry for biomedical applications. (December 2016) - Shi, Lin; Wang, Lin; Chen, Junjian; Chen, Jiongrun; Ren, Li; Shi, Xuetao; Wang, Yingjun
Graphical abstract: Abstract: In this article, the synthesis, cytocompatibility and antibacterial properties of short peptide modified graphene oxide (GO) were presented. The materials were prepared via Cu (I)-catalyzed azide-alkyne cycloaddition (CUAAC) click reaction. Click reaction is an efficient synthesis method without damaging the bioactivity of grafted short peptide. Two different peptides (RGD (arginine-glycine-aspartic acid) and AMP (antimicrobial peptide)) were used to modify GO in this work. Compared with pristine GO, the RGD modified GO was endowed with better biocompatibility, while the AMP modified GO performed excellent sterilization property. This report of short peptide modified GO materials may provide an innovative strategy for the biomedical applications of GO.